DOI: 10.3384/diss.diva-132424
|View full text |Cite
|
Sign up to set email alerts
|

Landfill Mining : Institutional challenges for the implementation of resource extraction from waste deposits

Abstract: Landfill mining is a term to describe the emerging field of exploring and extracting disposed material. The recovery of deposited resources may increase the flows of secondary resources and thereby replace a significant share of the primary production. The extraction of deposited materials may also be integrated with remediation and after care measures, to handle the many problematic landfills. Such unconventional recycling practices are, however, currently limited. The research in the field has mainly focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 95 publications
(183 reference statements)
0
8
0
Order By: Relevance
“…Article IV also finds that the socio-material perspective of the material creates disincentives for fines valorisation due to the perceived material complexity of fines, which is substantiated via one of the key empirical findings of Article II, that is, material characteristics of fines in terms of the distribution of average and variation of chemical and physical composition across incremental size fractions. Even though it is not common in the waste literature and totally lacking in fines research, certain previous studies, for example, landfill mining (Johansson, 2016), have emphasised its significance towards initiating valorisation investments by actors. Such knowledge is particularly helpful in identifying the need for increased societal awareness on the resource potential of fines, and thereby, having market actors and policymakers recognise the significance of its valorisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Article IV also finds that the socio-material perspective of the material creates disincentives for fines valorisation due to the perceived material complexity of fines, which is substantiated via one of the key empirical findings of Article II, that is, material characteristics of fines in terms of the distribution of average and variation of chemical and physical composition across incremental size fractions. Even though it is not common in the waste literature and totally lacking in fines research, certain previous studies, for example, landfill mining (Johansson, 2016), have emphasised its significance towards initiating valorisation investments by actors. Such knowledge is particularly helpful in identifying the need for increased societal awareness on the resource potential of fines, and thereby, having market actors and policymakers recognise the significance of its valorisation.…”
Section: Discussionmentioning
confidence: 99%
“…While having favourable institutional conditions is fundamental to the success of every industry (Wrigley, 1962), specific policy interventions could be particularly beneficial for potential new developments. In particular, cases such as potential fines valorisation do not have apparent direct market advantages for the participating individual actors due to the inferior material quality and low user demand, but only for society due to any environmental benefits (Johansson, 2016). Hence, governmental interventions are likely necessary to drive investments towards knowledge and technology development for upgrading and resource recovery as well as the utilisation of fines-derived SRMs.…”
Section: Socio-technical Systems Perspectivementioning
confidence: 99%
“…As waste pickers provide the vital and basic service of collecting MSW in places where the formal recycling sector is absent or highly ineffective (Agunwamba 2003), they contribute to turning waste into a resource and therefore contribute to increasing resource efficiency and closing the loop in a circular economy through reuse, recovery and recycling processes (Scarlat and Dallemand 2019). Johansson (2016) indicated that one way to increase recycling would be to focus on metals stocks often neglected in discussions about resource availability and the circular economy, since landfills and dumpsites have a great resource potential. For example, globally the amount of copper metal lost to the environment is estimated to be comparable with current in-use stocks.…”
Section: Contribution To the Circular Economymentioning
confidence: 99%
“…Van Passel et al 2013;Lederer, Laner, and Fellner 2014), and (v) "the role and responsibilities of institutions and other stakeholders involved in ELFM activ-ities" (e.g. Krook, Svensson, and Eklund 2012;Johansson 2016). While the first theme (i) was chosen to identify the general approach of participants to landfills and ELFM, the second, third and fourth themes (ii-iv) aim at analyzing the perceived sustainability of ELFM.…”
Section: The Interview Guidementioning
confidence: 99%